Recent Complicated Childbirth Aid Protocol Inspired by Luba-Kasai Therapeutic Practice - Augustin Mubiayi Mamba (New Frontiers in Medicine and Medical Research Vol. 5, 2021)
Improved maternal health remains a major concern of the United Nations in general and of the World Health Organization in particular, which have placed an important place on the Millennium Development Goals (MDGs) as well as in the objectives for Sustainable Development (SDO). Curiously, among the causes of complications of childbirth and pregnancy, the emphasis is more on physiological than psychosocial deaths, whereas in our least developed countries, where the percentage of maternal is mortality, cultural and psychological problems expose women to unwanted pregnancies and psychic traumas that manifest themselves during parturition in the form of eclampsia, haemorrhage and work defects, thus leading the woman and her baby to the risk of death. In the present work, we have proposed a protocol to help childbirth, inspired by the therapeutic practices of our African cultures. Indeed, our ancestors were able to solve the complications of childbirth by speech. The interview with woman with complications around her life and relationships triggered a kind of catharsis in the latter, the labor of childbirth was normal again and the delivery was normal. The protocol comprises three components: psychodynamic interview, prophylactic psychoeducation, psychological support. This protocol is based on the humanistic theories of Carl Rogers and Maslow and the sophrology of Alfonso Caycedo and consists in subjecting the parturient to a relaxation exercise by alternate breaths and haptonomy in a helping relationship to allow communication between the woman and her child who is to be born. This study will have the merits of integrating our complicated childbirth assistance protocol into the psychotherapy arsenal already in place, in order to rightly improve maternal health in childbirth.